2009
DOI: 10.1093/ndt/gfp175
|View full text |Cite
|
Sign up to set email alerts
|

Increased basal myocardial perfusion in patients with chronic kidney disease without symptomatic coronary artery disease

Abstract: Coronary flow reserve was normal although baseline myocardial blood flow was increased in all CKD patients as compared to healthy controls. Peripheral endothelial dysfunction was detected in all patients. Our findings suggest that coronary perfusion and peripheral vascular function are disturbed by different mechanisms in patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
1
19
2
Order By: Relevance
“…20 However, they found that differences in age and sex were largely responsible for the observed differences in CFR. A similar study by Koivuviita et al 21 in 21 CKD patients and 10 control subjects without signs or symptoms of CVD who underwent myocardial PET imaging also did not find a significant association between CFR and CKD, although there was a trend toward low CFR with more significant CKD. In contrast, a study using transthoracic echocardiography in a cohort of 10 dialysis patients and 14 matched control subjects with normal coronaries, found that both peak flow and CFR were below normal in 50% of the dialysis patients compared with only 5% of control patients.…”
Section: Discussionmentioning
confidence: 58%
“…20 However, they found that differences in age and sex were largely responsible for the observed differences in CFR. A similar study by Koivuviita et al 21 in 21 CKD patients and 10 control subjects without signs or symptoms of CVD who underwent myocardial PET imaging also did not find a significant association between CFR and CKD, although there was a trend toward low CFR with more significant CKD. In contrast, a study using transthoracic echocardiography in a cohort of 10 dialysis patients and 14 matched control subjects with normal coronaries, found that both peak flow and CFR were below normal in 50% of the dialysis patients compared with only 5% of control patients.…”
Section: Discussionmentioning
confidence: 58%
“…Chade et al used coronary flow wires to measure mid left anterior descending artery coronary flow reserve in patients without significant coronary disease, and found no independent association between CKD and a low flow reserve (25). A similar study by Koivuviita et al, which included 31 individuals (21 with CKD) without cardiovascular disease who underwent myocardial positron emission tomography, also did not show a significant association between nuclear flow reserve and CKD (26). In the context of these prior investigations, our findings raise new questions about animal models that have consistently demonstrated microvascular dropout in the myocardium of uremic animals (17,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 97%
“…Their study enrolled patients with various stages of CKD but at relatively small numbers. No specific exclusion of subjects with regional perfusion abnormality was performed, although the contribution of macroscopic disease and ischemia was probably low because of lack of decreased stress flow (30).…”
Section: Discussionmentioning
confidence: 99%